2006
DOI: 10.1161/01.hyp.0000236647.55200.07
|View full text |Cite
|
Sign up to set email alerts
|

Nox2, Ca 2+ , and Protein Kinase C Play a Role in Angiotensin II-Induced Free Radical Production in Nucleus Tractus Solitarius

Abstract: Abstract-The dorsomedial portion of the nucleus tractus solitarius (dmNTS) is the site of termination of baroreceptor and cardiorespiratory vagal afferents and plays a critical role in cardiovascular regulation. Angiotensin II (Ang II) is a powerful signaling molecule in dmNTS neurons and exerts some of its biological effects by modulating Ca 2ϩ currents via reactive oxygen species (ROS) derived from reduced nicotinamide-adenine dinucleotide phosphate (NADPH) oxidase. We investigated whether a Nox2-containing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
107
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 104 publications
(113 citation statements)
references
References 59 publications
3
107
0
3
Order By: Relevance
“…Within dendrites, the major site of NADPH oxidase subunit immunolabeling in dmNTS neurons, p47 phox immunoreactivity was associated with intracellular organelles that are involved in protein transport and calcium signaling, particularly ER-like tubulovesicular organelles, which were frequently associated with the outer mitochondrial membrane. Thus, p47 phox immunolabeling in dendritic smooth ER, which are sites for calcium storage and release, is consistent with physiological evidence that calcium currents in dmNTS neurons are modulated by superoxide produced by NADPH oxidase (23,47,48). In addition to intracellular sites, p47 phox immunolabeling was also seen at synaptic and extra-synaptic areas of the plasmalemma, similar to other reports in the literature indicating that NADPH oxidase has a synaptic distribution in other brain regions (41).…”
Section: Dendritic P47 Phox Labeling In Dmnts Neurons Of Saline Adminsupporting
confidence: 90%
See 2 more Smart Citations
“…Within dendrites, the major site of NADPH oxidase subunit immunolabeling in dmNTS neurons, p47 phox immunoreactivity was associated with intracellular organelles that are involved in protein transport and calcium signaling, particularly ER-like tubulovesicular organelles, which were frequently associated with the outer mitochondrial membrane. Thus, p47 phox immunolabeling in dendritic smooth ER, which are sites for calcium storage and release, is consistent with physiological evidence that calcium currents in dmNTS neurons are modulated by superoxide produced by NADPH oxidase (23,47,48). In addition to intracellular sites, p47 phox immunolabeling was also seen at synaptic and extra-synaptic areas of the plasmalemma, similar to other reports in the literature indicating that NADPH oxidase has a synaptic distribution in other brain regions (41).…”
Section: Dendritic P47 Phox Labeling In Dmnts Neurons Of Saline Adminsupporting
confidence: 90%
“…In the NTS, previous ultrastructural evidence indicates that NADPH oxidase subunits p47 phox, gp91 phox , and p22 phox are present in association with endomembranes, as well as the plasmalemma in neurons (16). In addition, previous neurophysiological results also indicate that functional NADPH oxidase potentiates AT-1A mediated calcium currents in dissociated second-order neurons in the dmNTS (47,48). The present results demonstrate that the subcellular distribution of p47 phox , and presumably functional NADPH oxidase-mediated superoxide production, is not spatially static, but subject to repartitioning in dendrites of dmNTS neurons in response to regimens of AngII or phenylephrine that produce a similar degree of hypertension.…”
Section: Repartitioning Of P47 Phox In Dendritic Profiles Of Dmnts Nementioning
confidence: 82%
See 1 more Smart Citation
“…This enzyme has been identified in subpopulations of neurons in many of the regions most susceptible to hypoxia/ reoxygenation injury: cortex, striatum, amygdala, hippocampus, and thalamus (Serrano et al, 2003). Apocynin, the NADPH oxidase inhibitor used in the present studies to prevent injury to wake-active groups, has been shown to protect against hippocampal ischemic injury in rodents (Wang et al, 2006). Whether NADPH oxidase inhibition will prevent hippocampal injury and memory impairments should now be examined.…”
Section: Discussionmentioning
confidence: 85%
“…7,23 Nox2-containing NAD(P)H oxidase in the NTS is the source of the Ang II-induced ROS generation in vitro. 23 Consistent with those studies, our results indicate that the Rac1/NAD(P)H pathway is involved in neuronal activation in the NTS and further indicate that activation of this pathway and the subsequent ROS generation in the NTS occur in the NTS of SHRSPs. More importantly, we demonstrated that the inhibition of Rac1 or overexpression of Cu/Zn-SOD in the NTS decreased blood pressure and HR in SHRSPs but not in WKYs.…”
Section: Discussionmentioning
confidence: 99%